Data Integration in the Life Sciences 10th International Conference, DILS 2014, Lisbon, Portugal, July 17-18, 2014. Proceedings - Galhardas, Helena; Rahm, Erhard (Springer eBooks, 2014)
This book constitutes the refereed proceedings of the 10th International Conference on Data Integration in the Life Sciences, DILS 2014, held in Lisbon, Portugal, in July 2014. The 9 revised full papers and the 5 short papers included in this volume were carefully reviewed and selected from 20 submissions. The papers cover a range of important topics such as data integration platforms and applications; biodiversity data management; ontologies and visualization; linked data and query processing.